Spray de quitosana na cicatrização de feridas cutâneas em ratas diabéticas - Santos, Thamiza Carla Costa dos (2016)
The healing is a complex and dynamic event aimed at the restoration of tissue integrity. However, some factors, such as diabetes, can harm this physiological event. Chitosan, a derivative of chitin, has been considered as a versatile and effective option for the treatment of wounds. This study aimed to evaluate and compare the effect of chitosan 2% gel and chitosan spray based on secondary intention healing of skin wounds in diabetic rats. 54 rats were used, divided randomly into three groups: control group (CG), chitosan 2% gel group (GG), and Chitosan spray group (GS) with 18 animals each. The rats in GC, GG, and GS had their wounds treated daily with saline solution 0.9%, chitosan 2% gel, and chitosan spray, respectively. The groups were divided into three subgroups (n = 6) according to the times of histological analysis of wound (third, seventh, and 14th day). The induction of diabetes in the rats took place by intraperitoneal application of alloxan (120 mg/kg). After confirming the state of diabetes, the animals were anesthetized and the wounds made with the aid of a punch 9.0mm in the dorsal region. Macroscopic and microscopic analyzes were performed. Macroscopic analysis showed that after 14 days, the chitosan 2% gel and chitosan spray gave a contraction rate of 100% and 99%, respectively. At the histological level, there was the anticipated recruitment of mononuclear cells, fibroblasia, and deposition of dense fibrovascular tissue and marked fibrosis in the wounds of GG and GS, emphasizing the ability of this biopolymer to optimize the healing of diabetics. It can therefore be a therapeutic option for the development of other formulations that provide wound repair in diabetic patients.